Does Right Issue Create A Value Change in Financial Performance? - Riris Rollyna Gultom (Jurnal Ekonomi LLDIKTI Wilayah 1 (JUKET), 2021)
The various results of research on the announcement of rights issues related to improving the financial performance of issuers through increasing share sales are interesting things to study, in line with additional capital, business expansion, paying debt obligations so that the company's performance continues to run. The purpose of this research is to determine the value of changes in the issuer's financial performance, namely current ratio, debt equity ratio, total assets turn over, net profit margin, return on equity and return on assets, before and after the rights issue was carried out on non-banking companies and financial institutions on the Stock Exchange Indonesian securities for the 2017-2020 period with a sample of 40 issuers. The results of this study use the Wilcoxon Signed Test T-test method where for the debt equity ratio proxy obtained sig (2-tailed) <0.05 which means the hypothesis is rejected, indicating a difference before and after the company conducts a right issue, while for the  proxy of current ratio, total assets turn over, net profit margin, return on equity and return on assets obtained sig (2-tailed)> 0.05 the hypothesis is accepted indicating there is no difference before and after the company conducts a rights issue.